Tāhlī-l āl-Akhto’ 'ālā Kītābātī āl-Jumlah āl-Fī’līyyāh fīī ād-Dārsīl Insyā’ Bīmā’hādī Dārīssālām Gontor līīl Bānāt āl-Hārom āts-Tsānī: - Rahmat Hidayat Lubis; Ahmad Nahidl Silmy; Ainun Jariah; Nur Julia Karlina; Nur Aprilda Mardhatillah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Error analysis refers to a type of linguistic analysis that focuses on the mistakes made by learners when learning a second language, and the classifying them. This research aims to analyze the errors in writing verbal sentences in composition lessons among second-year students at the Islamic Teacher Training College at Modern Islamic Boarding School Darussalam Gontor for Girls Campus 2. This research is a library research using descriptive and analytical methods, where data is obtained from the student’s notebooks collected to be analyzed afterwards to determine the types of errors that occur frequently and the factors that lead to these errors. The result of the research is that there were errors in the parsing of the direct object 17 times, in the parsing of the subject 6 times, in the parsing of the direct object of the adjective and the accusative twice, in the parsing of the present tense after the accusative letter 3 times, in the composition of the infinitive with that and the verb once, and in the use of the matching pronoun, once in the subject, once in the parsing of nullifying verbs, and once in the parsing of the genitive noun. In this abstract we will discuss the error analysis of writing Arabic and the best way of using good rules in writing verbal sentences so as not to fall into error writing. For future researchers, they can develop their learning strategies and they can be regenerated to be more complete for further research. Researchers suggest that future research places more emphasis on implementation and focuses on increasing the achievement of the values and ultimate goals of good Arabic language writing skill.